Dampak Desentralisasi Fiskal di Indonesia terhadap Pertumbuhan Ekonomi dan Disparitas Antar Daerah: Analisa Model Makro Ekonometrik Simultan - Dartanto, Teguh; Brodjonegoro, Bambang P. S. (Jurnal Ekonomi dan Pembangunan Indonesia, 2003)
From January 1, 2001, when new autonomy laws were implemented. Indonesia began to move toward decentralization of what had been a highly decentralized. This policy adopts two complimentary laws. Law No. 22/1999, which basically the devolution policy, has been accompanied by Law No. 25/1999, which basically reflect that decentralization policy in Indonesia has adopted the concept of "money follows function". Law No. 25/1999 describe the fiscal decentralization process that will create a new intergovernmental transfer scheme between the central government and local government. Some of items in the law were really new ones such as the natural resources revenue sharing, income tax sharing, general allocation fund (GAF) and specifics allocation fund (SAF). The policies of tax and natural resource revenue sharing can result in fiscal imbalance among regions. Tax and natural resources revenue sharing will benefit only to urbanized and natural resources rich regions Because of it, Central Government created General Allocation Funds. This fund has block grant characteristic and will be given to regions by fiscal gap conception. The purpose is to equalize fiscal capacity among regions that in tum also can reduce disparity among them. The Simultaneous Macro Econometric Model is made for analyzing the fiscal decentralization impact to economic growth and region disparity. The policy simulation in this model used transfer fund from central government such as Tax Revenue Sharing, Natural Resource Revenue Sharing and General Allocation Fund. The simulation is carried out to see the optimality of various possible existing policies. The optimality is measured by evaluating the high rate of economic growth and low disparity.